2021
DOI: 10.2215/cjn.15841020
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Mineralocorticoid Receptor Antagonists in Kidney Failure Patients Treated with Dialysis: A Systematic Review and Meta-Analysis

Abstract: Background and objectivesPatients with kidney failure have a high risk of cardiovascular disease due to cardiac remodeling, left ventricular fibrosis, and hyperaldosteronism, all of which can be potentially mitigated by mineralocorticoid receptor antagonists. However, because of the fear of hyperkalemia, the use of mineralocorticoid receptor antagonists in patients with kidney failure is limited in current clinical practice, and few studies have investigated the efficacy and safety. Thus, we aimed to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The most commonly used drugs in both groups were beta-blockers, statins, and erythropoietin, as well as immunosuppressive drugs for transplant patients.Using a cardioselectiveblocker in ESRD patients with dilated cardiomyopathy reduced sudden cardiac death, whereas correction of anaemia with erythropoietin substitution had no significant beneficial effect on LVH [28]. Also, statin treatment reduced the risk of a major cardiac event in KTx, but its relationship with the regression of left ventricular mass was not investigated [29].…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used drugs in both groups were beta-blockers, statins, and erythropoietin, as well as immunosuppressive drugs for transplant patients.Using a cardioselectiveblocker in ESRD patients with dilated cardiomyopathy reduced sudden cardiac death, whereas correction of anaemia with erythropoietin substitution had no significant beneficial effect on LVH [28]. Also, statin treatment reduced the risk of a major cardiac event in KTx, but its relationship with the regression of left ventricular mass was not investigated [29].…”
Section: Discussionmentioning
confidence: 99%
“…Because the kidney plays a critical role in controlling potassium balance, hyperkalemia is a common finding in patients with chronic kidney disease and has been associated with an increased risk for adverse cardiovascular events [44,45]. The association between plasma potassium levels and morbidity/mortality in HD patients has also been discussed [46,47]. The nitrate-rich BJ used in the current study contains relatively high levels of potassium (850 mg/70 mL), and therefore, we devoted particular attention to plasma concentration of potassium over time.…”
Section: Discussionmentioning
confidence: 99%
“…31,34 In a meta-analysis evaluating the benefits and side effects of mineralocorticoid receptor antagonists in renal failure patients undergoing dialysis, 14 eligible randomized controlled trials from 2005 to 2020 were included, with a total of 1309 participants. 35 The study showed that mineralocorticoid receptor antagonists may improve clinical outcomes in patients with renal failure without significantly increasing the risk of hyperkalemia. The safety of taking spironolactone in hemodialysis patients benefits from a steady potassium level in the body, and it must be emphasized that these patients undergo strict drug treatment monitoring throughout the process.…”
Section: Safety Of Spironolactone In Hemodialysis Patientsmentioning
confidence: 99%